Serum β-hCG Levels Between 13-20 Weeks Gestation Can Predict Development of Pregnancy Induced Hypertension - Kour, Gurpreet; Kour, Sandeep (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To find out predictive value of Serum β Human Chorionic Gonadotropin (β HCG) levels between 13-20 weeks of gestation in predicting the development of pregnancy induced hypertension (PIH) or pre-eclampsia, eclampsia. Methods: Serum β HCG level was estimated in 200 normotensive patients between 13-20 weeks of gestation. The median value of Serum β HCG was calculated and patients were divided into two groups as per two times Multiple of Median (2MOM) values of Serum β HCG i.e. those above and below the 2MOM values. The patients were followed up to delivery and were evaluated for the development of PIH, pre-eclampsia and eclampsia. Results: As per the median score of Serum β HCG in studied patients, the determined value of 2MOM was 30845 mIU/ml. Out of 200 patients, 23 (11.5%) patients were found to have values of Serum β HCG ≥ 2MOM. Twelve (52%) patients in Serum β HCG ≥ 2MOM group developed hypertension on follow up as compared to 13 (7.3%) patients in < 2MOM group (p< 0.0001). Also patients in the ≥ 2MOM group had higher prevalence of maternal and fetal complications. Conclusion: Serum β HCG levels between 13-20 weeks of gestation can predict development of PIH in pregnant females